Dicionário terminológico da inclusão das pessoas com deficiência - Mamus, Priscilla Teixeira (2017)
This Thesis aims to present, under a epistemological point of view, the existence of an area of knowledge called inclusion of people with disabilities, inclugindg wih the elaboration of a terminological dictionary. To this purpose, the author follows the theoretical-methodological perspective of the Communicative Theory of Terminology (TCT), by developing the following steps: an epistemological study of inclusion, which shows that the area brings together knowledge of several theories and fields of study, and how values and concepts have undergone changes in the course of movements for inclusion; organization of the corpus, formed by 439 digitized texts and submitted to the Unitex program, for the search of cadidates to terms that make up the dictionary; elaboration of the conceptual structure, an important methodological resource not only to facilitate the work of the terminologist, but also to assist him, as well as the consultant, in understanding and delimiting the field of study; elaboration of terminological records; writing of definitions of terms. The delimitation of concepts related to the inclusion of people with disabilities through Terminology contributes not only to the knowledge of this new specialty language, but also to show how language carries the values and concepts of a society and time, and how the inclusion of people with disabilities has terms whose concepts must be widely known, so that all citizens are agents of inclusion.